FAKTOR â FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI SEMARANG (Survei Pada Kantor SAMSAT Di Semarang) - Nur Subandiyah, 12.05.52.0164; Kartika, Andi (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of consciousness taxpayers, tax knowledge, quality of service and tax penalties on tax compliance in paying taxes on motor vehicles in Semarang SAMSAT Office. The entire study population registered taxpayers in SAMSAT Semarang, whereas sample, 113 people qualify as respondents. The process of collecting data from respondents conducted by distributing questionnaires to 130 corporate taxpayers with incidental sampling technique. Test instruments used are validity and reliability. Data were tested using multiple linear regression, the determinant test, F test (Goodness of Fit), and hypothesis testing using t test.Keywords: Tax Compliance, Awareness of Taxpayers, Tax Knowledge, Quality of Service and Tax Penalties